2013
DOI: 10.1002/j.2161-007x.2013.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Behaviors for Addressing Religious/Spiritual Issues: Do We Practice What We Preach?

Abstract: To determine if counselors integrate clinical behaviors for addressing religious/spiritual issues in counseling consistent with their ratings of the importance of such behaviors, the authors conducted a national survey of American Counseling Association (ACA) members. Seventy-eight ACA members rated the importance of and frequency with which they engaged in a set of 30 clinical behaviors that were identified in the existing literature as addressing religious/spiritual issues within counseling. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 10 publications
(14 reference statements)
1
29
1
Order By: Relevance
“…Although all average ratings were above slightly important (3.0), none reached moderately important (5.0). Thus, the college counselors in our study perceived the importance of religious and spiritual elements slightly lower than did counselors in Cashwell et al's () study, who rated the importance of religious and spiritual behaviors to be above average. It is possible that the college setting affected the importance ratings in our sample given that participants may have experienced perceived or actual environmental limitations regarding the discussion of religion and spirituality with students.…”
Section: Discussioncontrasting
confidence: 74%
“…Although all average ratings were above slightly important (3.0), none reached moderately important (5.0). Thus, the college counselors in our study perceived the importance of religious and spiritual elements slightly lower than did counselors in Cashwell et al's () study, who rated the importance of religious and spiritual behaviors to be above average. It is possible that the college setting affected the importance ratings in our sample given that participants may have experienced perceived or actual environmental limitations regarding the discussion of religion and spirituality with students.…”
Section: Discussioncontrasting
confidence: 74%
“…Delaney, Forcehimes, Campbell, and Smith () suggested that counselors working with substance abuse issues can integrate spirituality into treatment by including the pursuit of spiritual disciplines into treatment plans and goals, making appropriate referrals to religious/spiritual leaders in the community, and using open‐ended questions to facilitate client meaning making (e.g., “What do you imagine God is like?” and “How do you understand your purpose in life?”; p. 190). Exploring the many facets of a client's religion and spirituality may prove to be beneficial when working with substance abuse issues; however, researchers found that counselors addressed client religious/spiritual issues less frequently than importance ratings would suggest (Cashwell et al, ). Barriers related to work settings, fear of imposing values, and counselor unease with the religious/spiritual topics attributed to this discrepancy (Cashwell et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The probability of mental health providers working with Muslims has increased in the last few decades, considering the local and global sociopolitical contexts (Council on American‐Islamic Relations, ; Pew Research Center, ). The American Counseling Association (American Counseling Association, ) code of ethics, the Association for Spiritual, Ethical, and Religious Values in Counseling competencies (Young & Cashwell, ), and many other researchers (e.g., Ackerman, Ali, Dewey, & Schlosser, ; Cashwell et al, ; Wiggins, ) state the importance of familiarity with clients’ belief systems.…”
Section: Understanding Islam and Muslimsmentioning
confidence: 99%